Folk Medicinal Plants Used for Treatment of Gynecological Disorders by Rural Population of Zorlu village (in Turkey) - Ergül Bozkurt, Arzu Ergül (Ethnobotany Research and Applications, 2021)
Background: This research deals with the indigenous medicinal plants used by rural population of Artvin-Borçka (Zorlu village), for the treatment of gynecological disorders. For this purpose, ethnomedicinal survey of Zorlu village in Turkey was carried out during 2008-2009. Methods: In the present study, a two-part survey was made. The first part of the survey was determined the folk medicine used for treatment of gynecological disorders. Second part of the survey were determined the ethnomedicinal uses of the plants. Results: Local inhabitants are extremely knowledgeable about the utilization of indigenous flora of the study area and konowledge about the treatment of gynecological disorders. As a result of the study 74 plant taxa belonging to 59 genera and 30 families were determined. These 74 plant taxa used the treatment of gynecological disorders. Information on 74 plant taxa with their botanical name, pharmacological activity, ethnomedicinal usage knowledges were provided. In additon, the pharmacological properties of these plant taxa such as antioxidant, antimicrobial, antibacterial, antitumor, antiviral, anxiolytic, antidepressant, anthelmintic, antimalarial, antidiabetic, anti-ınflammatory, analgesic, tumor-ınhibitory, antiallergic, antihepatotoxic, antiulcer, anticandidal, antifungal, anticancer, antibiotic, anticariogenic, antigenotoxic, antirheumatic, antipruritic and antihypertensive activities are presented in this study. Conclusions: Present study is about the utilization of medicinal plants in Zorlu Village, they were used the traditional knowledge for the treatment of gynecological disorders. Documentation of such ethnomedicinal data on biological resources will can be used for medical and pharmaceutical science. Keywords: Turkey, medicinal plants, ethnomedicine; gynaecological disorders.